Lecturer Performance Information System Based on Reporting at STMIK Methodist Binjai Using Model Driven Architecture Method - Alamsyah, Reza (Bahasa Indonesia, 2023)
Information is a result of data processing, which is in the form of output that can be useful for people who need information in determining further decisions. The system is something that works together as a unit and depends on each other in order to achieve predetermined goals in a particular business. Model Driven Architecture (MDA) is an application development mechanism without using coding. STMIK Methodist Binjai is one of the universities in Binjai, which participates in conducting performance appraisals of lecturers. The lecturer performance information system at STMIK Methodist Binjai can make it easier for the campus to assess lecturer performance. With this application, the UPM can make it easier to monitor lecturers every semester, make it easier for lecturers to report lecturer performance periodically every semester and help the Campus.